2017
DOI: 10.1161/jaha.116.004749
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Worsened Metabolic Syndrome on the Risk of Dementia: A Nationwide Cohort Study

Abstract: BackgroundThe relationship of alteration of metabolic syndrome (MetS) with dementia remains unclear. The purpose of study was to evaluate the association between dynamic change in MetS status around a 5‐year period and dementia.Methods and ResultsThe cohort study was conducted from the Taiwanese Survey on Prevalence of Hypertension, Hyperglycemia, and Hyperlipidemia in 2002, with follow‐up in 2007. The sample was subsequently linked to the National Health Insurance Research Database. Participants were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 41 publications
(50 reference statements)
2
17
1
Order By: Relevance
“…We showed that an improvement of MS status was associated with reduced occurrence of dementia. This result is consistent with a previous study [13], in which an improved group showed less risk of dementia than a persistent MS group. Furthermore, we demonstrated that among MS components, fasting glucose and blood pressure were most important for risk reduction.…”
Section: Discussionsupporting
confidence: 93%
“…We showed that an improvement of MS status was associated with reduced occurrence of dementia. This result is consistent with a previous study [13], in which an improved group showed less risk of dementia than a persistent MS group. Furthermore, we demonstrated that among MS components, fasting glucose and blood pressure were most important for risk reduction.…”
Section: Discussionsupporting
confidence: 93%
“…4,5 Cardiometabolic abnormalities include cardiovascular risk factors such as central obesity, raised triglycerides, low high-density lipoprotein (HDL) cholesterol, hypertension, high blood glucose, and increased inflammation. [8][9][10][11][12] Some studies indicate cardiometabolic abnormalities increase the risk of dementia, 9,12 whereas others find no association. [8][9][10][11][12] Some studies indicate cardiometabolic abnormalities increase the risk of dementia, 9,12 whereas others find no association.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 However, the evidence-base regarding the association of cardiometabolic abnormalities with cognitive decline and incident dementia is mixed. [8][9][10][11][12] Some studies indicate cardiometabolic abnormalities increase the risk of dementia, 9,12 whereas others find no association. 10,11 Some researchers, instead, propose that individual markers of cardiometabolic abnormalities are linked with dementia rather than combined cardiometabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this 6-year prospective study aimed to investigate the association of MetS with the incidence of TNs in Chinese adults. Since the MetS status is known to change dynamically (18)(19)(20), we also explored whether the development of or recovery from MetS is associated with an altered risk for TNs.…”
Section: Introductionmentioning
confidence: 99%